Usability and acceptability of a fall monitoring system - Gonzalez Vega, Narciso (2017)
Falls and injurious falls affect one third of the older people. Those experiencing a fall might be unable to call for help remaining unattended for a long time. Pain, hypothermia and dehydration are common consequences. Additionally, ensuing fear of falling may reduce physical activity leading to functional decline and possibly institutionalization. Monitoring fall events the CONFIDENCE system could summon emergency assistance automatically thus reducing the negative consequences of falls.